The typographic characteristics of the german-brazilian journal Deutsche Post in 1884 - Silva, Dennis Messa (InfoDesign, 2022)
This work consists of a graphic analysis of the german-brazilian newspaper Deutsch Post (German Mail), in the editions published in 1884 and distributed in the region close to the municipality of São Leopoldo, RS – Brazil. In order to identify the main typographic styles and their present visual characteristics, were consulted publications physically available in the collection of the Visconde de São Leopoldo Museum. Through this procedure, it was possible to classify the different visual aspects found. Adaptations were also detected in the production and specific graphic manifestations of the publication in question. The newspaper, printed in German, is visually characterized by the Blackletter style typography, in which the Fraktur typeface is used in paragraph texts. The use of the respective alphabet design and other variants are predominant, as well as the graphic representations common to its time, the 19th century. The role of gothic letters in this periodical has the function of visually representing the german voice, while the types of roman latin aspect – present in part of the publication – are in charge of effecting the contrast with the portuguese language.